SIFAT ORGANOLEPTIK HARD CANDY SUSU DENGAN JENIS GULA BERBEDA - Prayogi, Dian (Universitas Merdeka Malang, 2016)
Hard candy is non-crystalline candy which is cooked with high temperature. This research aim is to find out the quality of organoleptic. Data was analyzed using variance investigation and DMRT. There was a real difference from hedonic quality test results. The result from hedonic test showed that hard candy milk with sugar cane was preferred flavor, the preferred color was hard candy milk with palm sugar, preferred texture was sugar cane, preferred clarity was palm sugar. Different kind of sugar will produce hard candy milk with real difference of flavor, color, texture and clarity. It is influenced by differences in the amount of sucrose and ash content on any kind of sugar.